Low cholesterol is not always good: low cholesterol levels are associated with decreased serotonin and increased aggression in fish - Aguiar, Ariane [UNESP]; Giaquinto, Percilia Cardoso [UNESP] (Company Biologists Ltd, 2018)
The inverse relationship between serum cholesterol and levels of aggression led to the cholesterol-serotonin hypothesis. According to this hypothesis, low dietary cholesterol intake leads to depressed central serotonergic activity, which is associated with increased aggression. Here we present the hypothesis about the evolutionary origins of low cholesterol and aggressive behavior, investigating the relationship between low levels of plasma cholesterol and aggressive behavior in fish. We used Nile tilapia (Oreochromis niloticus), a species of aggressive fish with a clear dominant subordinate relation, as an experimental model. The fish were treated with statin, a cholesterol-lowering drug. Aggressive behavior, brain serotonin (5-HT) concentrations, 5-hydroxyindoleacetic acid (5-HIM, the major 5-HT metabolite) and plasma cholesterol were analyzed after chronic administration of statin. Our results show that fish treated with statin exhibited reduced plasma cholesterol, reduced telencephalic indexes of 5-HIAA/5-HT and increased aggressive behavior compared to control fish. These results indicate that changes in plasma cholesterol may affect neurochemical processes underlying aggressive behavior in fish, suggesting an evolutionary mechanism conserved among vertebrates. Such mechanisms may be important for the control of aggression in many vertebrate species, not just mammals, as has been demonstrated so far.
Keywords: Plasma cholesterol; Aggressive behavior; Dominance hierarchy; Serotonergic action; Stalin